Income Distribution, Fertility Decisions and the Shadow Wage Rate: Implications of a New Approach to Rural-to-Urban Migration in LDCs - Oded Stark (Economic and Demographic Change: Issues for the 1980s. Proceedings of the Helsinki 1978 Conference, 1979)
This paper presents the outline of a new approach to the theory of rural-to-urban migration in less developed countries. Implications of the approach for inequality in the distribution of income, fertility decisions, and the shadow wage rate are explored.
Keywords: 330